Tissue-engineered cartilage constructed by a biotin-conjugated anti-CD44 avidin binding technique for the repairing of cartilage defects in the weight-bearing area of knee joints in pigs. Issue 5 (May 2017) - Lin, H.; Zhou, J.; Cao, L.; Wang, H.R.; Dong, J.; Chen, Z.R.
Abstract : Objectives: The lack of effective treatment for cartilage defects has prompted investigations using tissue engineering techniques for their regeneration and repair. The success of tissue-engineered repair of cartilage may depend on the rapid and efficient adhesion of transplanted cells to a scaffold. Our aim in this study was to repair full-thickness defects in articular cartilage in the weight-bearing area of a porcine model, and to investigate whether the CD44 monoclonal antibody biotin-avidin (CBA) binding technique could provide satisfactory tissue-engineered cartilage. Methods: Cartilage defects were created in the load-bearing region of the lateral femoral condyle of mini-type pigs. The defects were repaired with traditional tissue-engineered cartilage, tissue-engineered cartilage constructed with the biotin-avidin (BA) technique, tissue-engineered cartilage constructed with the CBA technique and with autologous cartilage. The biomechanical properties, Western blot assay, histological findings and immunohistochemical staining were explored. Results: The CBA group showed similar results to the autologous group in biomechanical properties, Moran's criteria, histological tests and Wakitani histological scoring. Conclusions: These results suggest that tissue-engineered cartilage constructed using the CBA technique could be used effectively to repair cartilage defects in the weight-bearing area of joints. Cite this article: H. Lin, J. Zhou, L. Cao, H. R. Wang, J. Dong, Z. R. Chen. Tissue-engineered cartilage constructed by a biotin-conjugated anti-CD44 avidin binding technique for the repairing of cartilage defects in the weight-bearing area of knee joints in pigs. Bone Joint Res 2017;6:–295. DOI: 10.1302/2046-3758.65.BJR-2016-0277.